التكامل المعرفي وقضايا التأصيل والتجديد al-Takamul al-Ma’rifi wa Qadaya al-Ta’sil wa al-Tajdid (integration of knowledge) and the issues of originality and renewal) - Ahmed Shogar, Ibrahim Adam (IIUM Press, 2013)
This book addresses prospects of integration of human knowledge and the issues of originality and revival.